Internet censorship detected in India (India) - Voidly (2026)
CRITICAL severity censorship detected in India. Confidence: 65%. Data sourced from CensoredPlanet.
Censorship Incident ID: IN-2026-0151
Keywords: censorship; IN; censorship; critical